THE CONCEPT OF STANYA APANAYANA (WEANING) - konapalli, *Jamuna; Krishnaiah, N. (International Journal of Ayurveda and Pharma Research, 2018)
The gradual replacement of breast milk and supplement of nutrients that is complimentary food is weaning. In Ayurveda it was explained under Stanya Apanayana concept. The World Health Organization defines complementary food as any food whether manufactured or locally prepared, suitable as a complement to breast milk or to infant formula, when either of them become insufficient to satisfy then nutritional requirements of the infant. Such food is also commonly called complimentary food. Breast feeding alone is sufficient for first six months of life, thereafter complementary foods are essential in order to maintain an adequate growth and development of the infant. The process of weaning and time period of weaning, role of weaning in growth and development of infant is explained in detail by Ayurvedic scholars as a concept of Stanya Apanayana. As per Ayurveda, stanya Apanayana is the process through which infant gradually changes from dependency of breast milk or formula to independence of it and starting solid foods. Supplementary feed of fruits is first described by Kashyapa at 6th month of life. No other author has described Phalaprasa. First cereal feed described in 6th month of age by Sushrutha and Vagbhbata. Cereal feed is prescribed at 10th month by Kashyapa -Dantha jatha i.e., after teeth eruption. Vagbhata accepted this opinion of Annaprasana after eruption of teeth but during 6th month of age. The cereals form the important part of diet in India. They form an important source of energy, carbohydrates, proteins, iron and also supply certain amount of fat. Hence the preparation with Shashtika Shali (a variety of rice which is harvested in 60 days) and other Dravyas such as Godhuma (wheat), Yava (barley) are best as complimentary food (along breast milk) explained in Kashyapa Samhitha.